Greenland Marine-Terminating Glacier Retreat Data - Wood, Michael; Rignot, Eric; Bjørk, Anders; van en Broeke, Michiel; Fenty, Ian; Menemenlis, Dimitris; Morlighem, Mathieu; Mouginot, Jeremie; Noël, Brice; Scheuchl, Bernd; Willis, Joshua; Zhang, Hong; et al. (Dryad, 2019)
The thinning, acceleration, and retreat of Greenland glaciers since the
mid-1990s has been attributed to the enhanced intrusion of warm Atlantic
Waters (AW) into fjords, but this assertion has not been quantitatively
tested on a Greenland-wide basis or included in numerical models. Here, we
investigate how AW influenced the retreat of 226 marine-terminating
glaciers by combining ocean modeling, remote sensing, and in-situ
observations. We identify 74 glaciers standing in deep fjords with warm AW
that retreated when ocean warming induced a 48% increase in glacier
undercutting that controlled 62% of the glacier mass loss in 1992-2017.
Conversely, 27 glaciers calving on protective, shallow ridges and 24
glaciers standing in cold, shallow waters did not retreat; and 10 glaciers
retreated when their floating sections collapsed. The mechanisms of ice
front evolution remain undiagnosed at 87 glaciers with no ocean and
bathymetry data, but these glaciers only account for 16% of the retreat.
Projections of glacier evolution that exclude ocean-induced glacier
undercutting may underestimate future mass losses by at least a factor
two.   In this dataset, we present data for 226 glaciers over the
time period 1985-2017. In particular, we provide estimates of glacier
geometry, ocean thermal forcing on the continental shelf and at the
glacier terminus, ice velocity, ocean-induced melt, and thinning-induced
retreat. Most of the data is compiled in a netCDF file for each of the 226
glaciers investigated durign the study period, with the exception of ice
front boundaries for the years 1985-2019 digitized from Landsat 5, 7, and
8 imagery, which we provide in a single shapefile. In addition, we include
a PDF which displays the data enclosed for each glacier.
Keywords: glacier; ice-ocean interactions; ice mass balance; ice front; ice front position; ice velocity; ice thinning; glacier melt